Citra Merek Sebagai Pemoderasi Pengaruh Promosi dan Kemudahan Penggunaan terhadap Minat Menggunakan Kembali ShopeePay - Sri Devi; Rindang Matoati (Universitas Serang Raya, 2022)
The digital economy has changed the way Indonesians transact from cash payments to non-cash payments, thus creating a cashless society trend that is in line with regulations related to electronic money. Electronic money can be divided into e-money (chip-based) and also e-wallets (server-based). E-wallet is one of the most widely used payment methods today because it offers various conveniences and benefits for its users. The most widely used digital wallet in Indonesia is ShopeePay. This study aims to analyze the influence of promotion and ease of use on intention to reuse ShopeePay with the brand image as a moderation variable. The population in this study are e-commerce Shopee users who have transacted using ShopeePay in Jabodetabek whose number are not known for certain. The sampling technique used purposive sampling with a total sample of 195 respondents and the data are analyzed using Structural Equation Modelling - Partial Least Square (SEM-PLS). The results showed that promotion has a positive and significant effect on the intention to reuse, ease of use has a positive and significant effect on the intention to reuse, brand image has a positive and significant effect as a moderation of the relationship between promotion and the intention to reuse, and brand image is not variable moderating for the relationship between ease of use and intention to reuse. Keywords: Brand image; E-Wallet; Ease f Use; Intention to Reuse; Promotion.